2013
DOI: 10.1117/1.jbo.18.12.126017
|View full text |Cite
|
Sign up to set email alerts
|

Vital-dye-enhanced multimodal imaging of neoplastic progression in a mouse model of oral carcinogenesis

Abstract: Abstract. In this longitudinal study, a mouse model of 4-nitroquinoline 1-oxide chemically induced tongue carcinogenesis was used to assess the ability of optical imaging with exogenous and endogenous contrast to detect neoplastic lesions in a heterogeneous mucosal surface. Widefield autofluorescence and fluorescence images of intact 2-NBDG-stained and proflavine-stained tissues were acquired at multiple time points in the carcinogenesis process. Confocal fluorescence images of transverse fresh tissue slices f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Unfortunately, the sensitivity of the VELscope for detecting malignancy and dysplasia has been reported to be from 30% to 100%, and the specificity ranges from 15.3% to 100% [5]. The mean intensity of 2-NBDG imaging which reflected increased metabolic activity of neoplastic cells, and the standard deviation of proflavine fluorescence intensity which revealed neolastic transformation by disorganized fluorescence intensity patterns from nuclei accompanying carcinogenesis, were found to be the best discriminative features for neoplasia detection [11]. However, our results suggested that classification with multiband fluorescence intensity was more accurate than the single band in both autofluorescence and fluorescence imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the sensitivity of the VELscope for detecting malignancy and dysplasia has been reported to be from 30% to 100%, and the specificity ranges from 15.3% to 100% [5]. The mean intensity of 2-NBDG imaging which reflected increased metabolic activity of neoplastic cells, and the standard deviation of proflavine fluorescence intensity which revealed neolastic transformation by disorganized fluorescence intensity patterns from nuclei accompanying carcinogenesis, were found to be the best discriminative features for neoplasia detection [11]. However, our results suggested that classification with multiband fluorescence intensity was more accurate than the single band in both autofluorescence and fluorescence imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirmed the value of combining autofluorescence and reflectance parameters together with the fluorescence of the dyes to provide images very close to conventional histology. Unfortunately, imaging tools able to produce such images are still homemade prototypes not equipped with a fiber optics probe able to access the oral cavity, and they are currently solely intended for skin imaging in mouse models or ex vivo human samples .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed procedures for vital dye fluorescence imaging methods were previously described in ref. 27. Here is a brief summary of the imaging procedures:…”
Section: Methodsmentioning
confidence: 99%